A difunctional azido-cobalt(ii) coordination polymer exhibiting slow magnetic relaxation behaviour and high-energy characteristics with good thermostability and insensitivity. Issue 35 (30th July 2018) - Ma, Xiaohui; Liu, Yaru; Song, Weiming; Wang, Zheng; Liu, Xiangyu; Xie, Gang; Chen, Sanping; Gao, Shengli
Abstract : As a difunctional material, an azido-Co(ii ) coordination polymer with a high-nitrogen content exhibits both molecule-based magnetic behaviour and high-energy performance with superior thermostability and insensitivity. Abstract : A novel one-dimensional azido-cobalt(ii ) compound, [Co2 (1-mbt)2 (N3 )4 ] n (1 ) (1-mbt = 1-((2-propyl-imidazol-1-yl)methyl)-benzo[1, 2, 3]triazole), was solvothermally synthesized. X-ray crystal structure analysis demonstrates that two crystallographically independent Co(ii ) atoms in the asymmetrical unit of compound1 exhibit a rectangular pyramid geometry. The 3D supermolecular network of1 consists of well-isolated 1D metal chains in which the azido bridging ligands assume an unusual pattern of combination with the Co(ii ) centre as the sign of [–EE–EO–EO–EO–] n . The various coordination modes of the azido anion are responsible for different magnetic exchanges between the adjacent Co(ii ) ions. The end-to-end (EE) mode mediates the antiferromagnetic coupling, whereas the end-on (EO) manner contributes to the ferromagnetic interaction. Magneto-structural relationships are discussed with the aid of theoretical calculations which are employed to find the potential single-ion magnetic anisotropy and reproduce the observed magnetic coupling properly. Alternating current magnetic susceptibility measurements reveal that1 features a typical behaviour of field-induced slow magnetic relaxation. Energetic characterization evidences that the resulting compound possesses satisfactory detonation properties, superior lack of sensitivity and thermostability owing to the high nitrogen content (N% = 40.10%) and a coherent intrachain configuration. The kinetic parameters of the exothermic processes for1 are investigated by the Kissinger method and the Ozawa method. We note that1 has potential application prospects as a new generation of environmentally friendly high-energy materials based on this nitrogen-rich and oxygen-free system. In addition, the compound is developed as a practical additive to promote the thermal decomposition of ammonium perchlorate (AP) and hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine (RDX). The finding in this work highlights an example of effective development of advanced magneto-energetic materials.